Vitamin D3 and B12 supplementation in pregnancy. (April 2021) - Bhowmik, Bishwajit; Siddiquee, Tasnima; Mdala, Ibrahimu; Quamrun Nesa, Liya; Jahan Shelly, Samsad; Hassan, Zahid; Moreira, Nayla Cristina do V.; Jahan, Ishrat; Azad Khan, A.K.; Hitman, Graham A.; Hussain, Akhtar
Highlights: WHO position not to recommend routine vitamin D supplementation during pregnancy. Deficiency of vitamin D and vitamin B12 are very common worldwide. Low Birth Weight is the single most risk factor for neonatal mortality, DM and CVD. However, contradicting evidence for vitamin D supplementation remains a dispute. There is an urgency to establish guidelines for vitamin D supplementation during pregnancy. Abstract: Aim: To assess the efficacy of vitamin D3 or B12 supplementation during pregnancy. Methods: Pregnant women at 6–14 weeks in the intervention arm received oral high dose intermittent vitamin D3 and/or low dose B12 supplementation if they had vitamin D or vitamin B12 deficiency. The control arm received prescribed dietary instruction only. An additional observational arm for those mothers at booking with normal vitamin D and vitamin B12 level was also recruited. All groups received standard care during pregnancy. Results: The primary endpoint of either vitamin D or B12 at term was not met. At baseline 25% participants in both the interventional and control arms had severe D deficiency (<30 nmol/l), reducing to under 3.4% in both groups. No maternal differences in vitamin D or B12 levels were found at delivery between the intervention, control, or observational groups. No significant difference in any of the pregnancy or birth outcomes was observed between three groups. Conclusions: In this study, oral supplementation of high dose intermittent vitamin D or low dose vitamin B12 regime failed to correct the relevant nutritional deficiencies in Bangladeshi pregnant women as per protocol. Both dietary supplementation and high dose vitamin D corrected severe vitamin deficiency.